Digoxin Therapy in Heart Failure and Atrial Fibrillation: A Pharmacotherapeutic Review for Pharmacists - Alshamrani, Hassan; Fayez Fayadh Helal Alanazi,; Fahd Omar Amer Al-Sahafi,; Adel Ali Al-Shehri,; Bejad Muteb Saad Al-Otaibi,; Sultan Abdullah Al-Qahtani,; Saud Nasser Salem Al-Otaibi,; Hussain Habib Al Abdullah,; Ali Hasan Ali Gharawi,; Ali Ibrahim Abdullah Faqeeri, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Digoxin, a cardiac glycoside derived from <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Digitalis lanata<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">, has been used for decades in managing heart failure and atrial fibrillation. Despite its historical prominence, its role has narrowed due to safer alternatives and concerns about toxicity. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide pharmacists with an updated understanding of digoxin’s pharmacology, clinical indications, dosing strategies, safety considerations, and monitoring requirements. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature review of FDA labeling, ACC/AHA guidelines, and recent clinical evidence was conducted to synthesize pharmacotherapeutic principles relevant to digoxin use in contemporary practice. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Digoxin remains FDA-approved for chronic atrial fibrillation and symptomatic heart failure with reduced ejection fraction. It improves symptoms and reduces hospitalizations but does not confer mortality benefit. Its dual mechanism—positive inotropy and AV nodal inhibition—supports its use for rate control and symptom relief. However, digoxin’s narrow therapeutic index, renal clearance dependence, and susceptibility to drug–drug interactions necessitate individualized dosing and vigilant monitoring. Toxicity manifests as gastrointestinal symptoms, visual disturbances, and life-threatening arrhythmias, with risk amplified by renal impairment and electrolyte imbalance. Digoxin immune fab remains the antidote for severe overdose. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Digoxin retains a niche role as adjunctive therapy in selected patients with heart failure or atrial fibrillation when first-line agents are unsuitable. Safe use requires conservative dosing, routine monitoring of serum levels, renal function, and electrolytes, and proactive management of interactions.